Reputation: 43
I have this expression: X'YZ'+X'YZ+XY'Z'+XYZ'+XYZ (' means not) I know the answer is Y+XZ' but I am stuck in the last part. Can anyone give me a hand?
This is what I got so far:
X'YZ' + X'YZ + XY'Z' + XYZ' + XYZ
X'YZ' + X'YZ + XZ'(Y' + Y) + XYZ
X'YZ' + X'YZ + XZ' + XYZ
X'YZ' + X'YZ + XYZ + XZ'
Y(X'Z' + X'Z + XZ) + XZ'
Y(1) + XZ' # I am not sure if is there is a rule that makes (X'Z+X'Z+XZ)= 1
Thanks
Upvotes: 3
Views: 2695
Reputation: 617
Beginning with X'YZ'+X'YZ+XY'Z'+XYZ'+XYZ
(¬X ∧ Y ∧ ¬Z) ∨ (¬X ∧ Y ∧ Z) ∨ (X ∧ ¬Y ∧ ¬Z) ∨ (X ∧ Y ∧ ¬Z) ∨ (X ∧ Y ∧ Z) ↔ ⊤
Construct a Karnaugh map http://en.wikipedia.org/wiki/Karnaugh_map
XY 00 01 11 10
Z 0 0 1 1 1
1 0 1 1 0
Reduce to Y ∨ (X ∧ ¬Z) in two steps.
Upvotes: 0
Reputation: 976
The only solution that I can think of is this (i.e. using XYZ'
twice):
X'YZ' + X'YZ + XY'Z' + XYZ' + XYZ
X'YZ' + X'YZ + XY'Z' + XYZ' + XYZ + XYZ'
X'YZ' + X'YZ + XZ'(Y' + Y) + XYZ + XYZ'
X'YZ' + X'YZ + XYZ + XYZ'+ XZ'
Y(X'Z' + X'Z + XZ + XZ') + XZ'
Y(1) + XZ'
Y + XZ'
Upvotes: 2